The association of monocyte-to-lymphocyte and neutrophil-to-lymphocyte ratios with CIMT in HD and CAPD populations - Baridwan, Fakhri; Samsu, Nur; Winoto, Eden (Deka in Medicine, 2025)
BACKGROUND: Chronic kidney disease (CKD) carries a high risk of cardiovascular complications due to atherosclerosis, which is exacerbated by chronic inflammation. The neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) are emerging inflammatory markers with potential to predict atherosclerotic risk. OBJECTIVES: To evaluate the association between NLR and MLR values with carotid intima-media thickness (CIMT) in CKD patients undergoing hemodialysis and continuous ambulatory peritoneal dialysis (CAPD). METHODS: This observational cross-sectional study was conducted at Dr. Saiful Anwar General Hospital, Malang, between July and December 2024. Data on baseline characteristics, laboratory results, and CIMT were obtained from medical records and carotid ultrasonography. Statistical analyses included t-tests, Mann-Whitney tests, and Pearson or Spearman correlation tests, depending on data distribution. RESULTS: A total of 97 CKD patients were included (45 on CAPD and 52 on hemodialysis). NLR values were significantly higher in the CAPD group compared to the hemodialysis group (p = 0.0253), while MLR did not differ significantly. CIMT was significantly higher in the hemodialysis group (p = 0.0035). In the CAPD group, MLR was significantly correlated with CIMT (r = 0.3543; p = 0.0169), whereas no significant correlation was observed in the hemodialysis group. NLR was not significantly associated with CIMT in either group. Subgroup and ROC analyses indicated that neither NLR nor MLR could accurately differentiate elevated CIMT from normal. CONCLUSION: MLR is associated with CIMT in patients undergoing CAPD, while NLR does not show a significant association with CIMT in either dialysis group.